Depression & Protectionism : Britain Between the Wars. - Capie, Forrest (Taylor and Francis, 2013)
Depression and Protectionism considers the case of the oldest advocate of free trade and its greatest exponent, Britain, and examines the developments that led to the reversal of that policy in the 1930s. It also discusses the consequences of the protectionst policy for the domestic economy. * Discusses the most important debate in international economics* Using an explicit economic framework, the book examines the economic origins of the industrial tariff in Britain.